PKM PELATIHAN PENINGKATAN KEMAMPUAN MENGKONVERSI SATUAN BAGI SISWA KELAS V SD INP 12/79 BIRU II WATAMPONE - Sudarto Sudarto; Firdaus Firdaus; Muh. Idris Jafar; Sitti Rahmi (Bajang Institute, 2023)
The goal would be achieved in this activity was increasing the ability and understanding of the 5th Grade students at SD Inp 12/79 Biru II Watampone in converting units and performing arithmetic operations related to these ones. The methods used in this service were lecture and simulation methods. The results of the service showed that the ability level of students (trainees) after attending the training in converting units was in good category and the weakness of students in converting units was about how to operate the decimal fractions as well as ordinary fractions and mixed fractions, especially in division operations.